In situ multiplex detection of serum exosomal microRNAs using an all-in-one biosensor for breast cancer diagnosis - Wang, Huizhen; He, Dinggeng; Wan, Kejing; Sheng, Xiaowu; Cheng, Hong; Huang, Jin; Zhou, Xiao; He, Xiaoxiao; Wang, Kemin (Analyst (London), 2020)
Herein, a simple all-in-one biosensor based on a DNA three-way junction has been constructed for in situ simultaneous detection of multiple miRNAs by competitive strand displacement. In our design, three oligonucleotides (Y1, Y2 and Y3) of a Y-type scaffold were extended at their 5′ ends by introducing three single-stranded recognition sequences with quenchers (BHQ1, BHQ2 and BHQ2), respectively. Subsequently, three reporter sequences labeled with different fluorophores (FAM, Cy3 and Cy5) were bound to the corresponding recognition sequences to form a multicolour DNA biosensor that gives self-quenched fluorescence. The biosensor can effectively enter into exosomes and then hybridize to the complementary miRNA targets to form longer duplexes and release the reporter sequences, thus activating the readable fluorescence signals for the simultaneous detection of multiple miRNAs in exosomes. As a proof of principle, miR-21, miR-27a and miR-375 were chosen as model targets because of their high expressions in breast cancer cells (MCF-7). Fluorescence signals of MCF-7 exosomes after being treated with the biosensor exhibited positive correlations to their concentrations and the limits of detection were determined to be 0.116 μg mL −1 , 0.125 μg mL −1 and 0.287 μg mL −1 for exosomes by detecting three exosomal miRNAs (miR-21, miR-27a and miR-375), respectively. In contrast, there were no obvious correlations between fluorescence intensities and control MCF-10A exosome concentrations. Importantly, by testing multiple exosomal miRNAs using the biosensor in clinical serum samples, breast cancer patients can be effectively differentiated from healthy donors. Consequently, the developed biosensor demonstrates high potential as a routine bioassay for the multiplex quantification of exosomal miRNAs in clinical diagnosis.